Improperly Delegated Consecration of a Vigrin: Canon 1169 - Anslow, Thomas (CLSA advisory opinions, 2001-2005, 2001)
Some time ago an auxiliary bishop, believing he had the authority to act without consulting the diocesan bishop, agreed to allow a certain petitioner to become a consecrated virgin as envisioned in canon 604. He delegated a presbyter to perform the rite of consecration, and he did so. Now the virgin is asking whether her consecration was valid.